Decentralized to Centralized Organizational Strategies for AI Integration in Finance - Müller, Johannes; Rossi, Sofia; Bianchi, Mateo (Journal of Theory and Practice in Engineering and Technology, 2024)
This article explores the burgeoning intersection of artificial intelligence (AI) and the financial sector, focusing on the transformative impact of large models and generative AI technologies. Amidst the ongoing digital revolution in finance, these technologies are revolutionizing traditional operational frameworks across banks, insurance firms, and securities brokers. The paper examines key applications such as risk management, fraud detection, personalized financial recommendations, and automated customer service, highlighting their potential to enhance operational efficiency and customer satisfaction. Drawing on McKinsey's projections of substantial economic value creation, the study also analyzes organizational structures adopted by financial institutions for AI integration, ranging from highly centralized to decentralized models. Ultimately, the research underscores the pivotal role of AI-driven innovations in reshaping financial services and outlines future directions for research and implementation in this dynamic field.